Original paperT regulatory CD4+CD25high lymphocytes in peripheral blood of patients suffering from psoriasis - Pawlaczyk, Mariola; Karczewski, Jacek; Wiktorowicz, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction: Psoriasis is a chronic T-cell mediated autoimmune skin disease. Recently, the role of T regulatory lymphocytes (Treg) CD4+CD25+ in the pathogenesis of psoriasis has been pointed out. Aim: To estimate the percentage of Treg lymphocytes CD4+CD25high in peripheral blood of patients with psoriasis in various stages of disease severity. Material and methods: The study was conducted on 50 patients divided into two groups: with mild and moderate (PASI ≤ 12) and severe (PASI > 12) psoriasis. The control group consisted of 15 healthy subjects. Treg cells were measured using flow cytometry with CD3, CD4, CD25 antibody. The mean percentage of Treg was 4.4 in the group of patients with severe clinical course of psoriasis, 7.01 in patients with mild and moderate stage of the disease, and 8.39 in the control group. Results: A statistically lower percentage of CD3+CD4+CD25 Treg lymphocytes was found in peripheral blood of patients with severe psoriasis in comparison with control healthy subjects (4.44 ±2.2 vs. 8.39 ±2.7, p 0.05). Examined patients suffering from psoriasis with PASI ≤ 12 differed statistically from patients with PASI > 12 in the percentage of Treg in peripheral blood. Conclusions: Psoriasis is characterized by an inflammatory process for which the activation of effector T lymphocytes is responsible. It seems that changes in percentages of Treg lymphocytes in peripheral blood may prove that the activation of the cells is defective.